Foreign Divestment in the Retail Sector – The Host Market's Perspective. (21st November 2018) - Gersch, Inka; Franz, Martin
Abstract: Transnational grocery retailers increasingly dispose of their foreign subsidiaries. The existing literature on this development mainly focuses on the perspective of transnational retailers on their own divestments, and neglects the view of the actors in the remaining market. Addressing this bias, this paper analyses the dynamics and drivers of foreign divestment from the host market perspective. It is based on data from qualitative interviews with host market competitors and sold subsidiaries of transnational retailers in Turkey. The research reveals that, while home market actors present their divestments as strategic decisions, for the host market's actors the TNCs' divestments are stories of failure. We propose a holistic framework of the foreign divestment decision process showing that a divestment decision is not just the inverse of an investment decision. This framework incorporates pull factors (reasons to reallocate resources), push factors (host market hurdles) and foreign retailers' possibilities to take on the challenges in foreign markets.